Female Directors Moderating the Effect of CSR, Company Risk, and Leverage on Tax Avoidance - Natasya; Ponziani , Regi Muzio (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study aims to provide empirical evidence on the influence of the independent variables’ corporate social responsibility, profitability, leverage, firm size, company risk, and audit quality, and the moderating variable, women directors, on the relationship between corporate social responsibility and tax avoidance. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange from 2022 to 2024. A purposive sampling method was used to select the sample, yielding 61 companies and 183 usable observations. The sample data were analyzed using moderated regression analysis, a specialized variant of multiple regression with SPSS Statistics 25. The results show that the independent variables profitability, leverage, and company risk affect tax avoidance. Meanwhile, corporate social responsibility, firm size, and audit quality do not affect tax avoidance, and the presence of women directors does not moderate the effect of corporate social responsibility on tax avoidance. These findings are expected to provide stakeholders with an overview of the condition of companies related to tax avoidance practices